Surviving Grounded Theory Research Method in an Academic World - Naomi Elliott; Agnes Higgins (Grounded Theory Review: An International Journal)
Grounded theory research students are frequently faced with the challenge of writing a research proposal and using a theoretical fram ework as part of the academ ic requirements for a degree program m e. Drawing from personal experiences of two PhD graduates who used classic grounded theory in two different universities, this paper highlights key lessons learnt which may help future students who are setting out to use the grounded theory method. It identifies key discussion points that students may find useful when engaging with critical audiences, and defending their grounded theory thesis at the final examination. Key discussion points included are: the difference between inductive and deductive inquiry; how grounded theory method of data gathering and analysis provide researchers with a viable means of generating new theory; the prim acy of the questions used in data gathering and data analysis; and, the research- theory link as opposed to the theory-research link.